WOMAN CAUGHT BETWEEN TRADITION AND MODERNITY A STUDY OF MULK RAJ ANAND’S THE OLD WOMAN AND COW - Trivedi, Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tradition and Modernity are essential components of the flow of human life. It is natural, therefore, that their respective meanings, importance in life and their clash that provides a major theme to the creative writing, be examined in the present paper. The term, tradition, has very close associations with human life and is used with reference to its various aspects. It influences man-to-man relationship and at the same time its impact on social life. Tradition derived from Latin word, means : “A long established and generally accepted custom or method of procedure, having almost the force of a law; and immemorial usage”.(1)